Window on freedom : race, civil rights, and foreign affairs, 1945-1988 - Plummer, Brenda Gayle (UNC Press law publications., 2003)
Demonstrates how US foreign policy has been embedded in social, economic and cultural factors of domestic and foreign origin. It argues that the campaign to realize full civil rights for racial and ethnic minorities in the US is best understood in the context of competitive international relations.